Tumores Mamarios En Hembras (Canis Lupus Familiaris) (2024)
One of the pathologies that occurs most frequently among the canine population are mammary tumors, which represent a significant concern in veterinary medicine due to their high incidence and impact on the quality of life of companion animals. Mammary tumors in canines are multifactorial, influenced by genetic, hormonal and environmental factors. Prolonged exposure to female sex hormones increases the risk of developing breast tumors. Additionally, certain breeds have a genetic predisposition to these tumors.